Sport facility and event management - Aicher, Thomas J.; Paule-Koba, Amanda L.; Newland, Brianna L. (Burlington, MA Jones & Bartlett Learning, 2016)
"Written with both the graduate and undergraduate student in mind, Sport Facility and Event Management focuses on the major components of both facility and event management planning, financing, marketing, implementation, and evaluation. It integrates timely theoretical foundations with real world practicality and application to provide the reader with a strong foundation in facility and event management. The authors focus on a broad range of facilities and events to demonstrate the diversity of the industry, which encompasses recreation, leisure, health and fitness, in addition to the more commonly discussed sport facilities and events."--Publisher's website.
1. Introduction and History -- 2. Management Theory -- 3. Facility Design and Construction -- 4. Finance and Budgeting -- 5. Bidding and Planning for Different Events -- 6. Designing the Event Experience -- 7. Project Management and Event Implementation -- 8. Marketing the Facility and Events -- 9. Consumer Behavior -- 10. Sponsorship -- 11. Traditional Revenue Generation in Sport and Recreation -- 12. Customer Service -- 13. Risk Management -- 14. Measurement and Evaluation -- 15. Sustainability and Legacy.
Includes bibliographical references and index.
Keywords: Sports facilities -- Management; Special events -- Management